2020
DOI: 10.1073/pnas.2001661117
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of peptidoglycan endopeptidase regulation

Abstract: Most bacteria surround themselves with a cell wall, a strong meshwork consisting primarily of the polymerized aminosugar peptidoglycan (PG). PG is essential for structural maintenance of bacterial cells, and thus for viability. PG is also constantly synthesized and turned over; the latter process is mediated by PG cleavage enzymes, for example, the endopeptidases (EPs). EPs themselves are essential for growth but also promote lethal cell wall degradation after exposure to antibiotics that inhibit PG sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 80 publications
1
46
0
Order By: Relevance
“…In all these cases, as well as in E. coli, β-lactams trigger autolysin release by disturbing the balance between peptidoglycan synthesis and hydrolysis, which is necessary for growth of the cell wall 54 . Bacterial growth requires constant synthesis and turnover of the cell wall to insert new molecules, and the latter process relies on peptidoglycan cleavage enzymes, including glycosidases, amidases and endopeptidases 55 . The same enzymes can produce lethal damage -the physiology of growth can be converted into the physiology of death.…”
Section: Death By Endogenous Disruption Of Cell Envelopesmentioning
confidence: 99%
“…In all these cases, as well as in E. coli, β-lactams trigger autolysin release by disturbing the balance between peptidoglycan synthesis and hydrolysis, which is necessary for growth of the cell wall 54 . Bacterial growth requires constant synthesis and turnover of the cell wall to insert new molecules, and the latter process relies on peptidoglycan cleavage enzymes, including glycosidases, amidases and endopeptidases 55 . The same enzymes can produce lethal damage -the physiology of growth can be converted into the physiology of death.…”
Section: Death By Endogenous Disruption Of Cell Envelopesmentioning
confidence: 99%
“…We have previously shown that EP depletion in the ∆6 endo strain results in a dramatic increase in cell diameter and ultimately the generation of giant, bulky and contorted cells (34). Here, we asked to what extent these enlarged cells accumulated a PG cell wall.…”
Section: Cell Wall Incorporation and Mass Increase Continue During Enmentioning
confidence: 93%
“…4A, 5A). However, we recently demonstrated that EPs from diverse organisms (including E. coli and N. gonorrhoeae) are produced in an inactive form due to the inhibitory function of their domain 1 and likely activated in vivo by an unknown mechanism (34). Heterologously expressed enzymes are likely not subject to this activation pathway in V. cholerae (especially if the activator is a protein) and we thus instead expressed EP mutant versions with their inhibitory domain 1 deleted, which are expected to be constitutively active.…”
Section: Mreb Movement Continues In Ep-insufficient Cellsmentioning
confidence: 99%
See 2 more Smart Citations